UNLOCKING THE TRENDS AND PATTERNS OF MIDAZOLAM RESEARCH: A BIBLIOMETRIC CRITICISM - Tushar Khachane; Bidhan Dolai (Student's Journal of Health Research, 2023)
Background: Understanding the research landscape surrounding midazolam is crucial for identifying the current state of knowledge and potential areas for further investigation. Methodology: This bibliometric review utilizes various bibliometric indicators to analyze and summarize the body of research on midazolam. A comprehensive search of relevant literature databases is conducted, and the retrieved publications are subjected to data analysis. Bibliometric indicators, such as frequently researched themes, frequently occurring keywords, influential and active journals, relevant and emerging topics, and trends over time, are examined to gain insights into the research landscape. Results: The most frequently researched themes include the clinical use of midazolam in anesthesia, sedation, and critical care, as well as its pharmacokinetics and pharmacodynamics. Frequently occurring keywords highlight topics such as adverse effects, drug interactions, and patient outcomes. Influential and active journals in the field are identified, indicating the key sources of research dissemination. Word cloud and trending topic analyses provide visual representations of the data, showcasing the prominent themes and emerging areas of interest. Conclusion: This bibliometric review provides a comprehensive overview of midazolam research and its trends and patterns over time. The findings demonstrate the importance of midazolam in clinical practice and research, highlighting the key areas of investigation and emerging topics. The analysis identifies knowledge gaps and potential areas for further research, contributing to the understanding of midazolam's effects, safety, and optimal use. Recommendations: Investigations into the long-term outcomes and efficacy of midazolam in different patient populations can provide valuable insights. Furthermore, interdisciplinary collaborations and knowledge exchange between researchers in anesthesia, pharmacology, and critical care can foster innovation and advance the understanding of midazolam. Finally, staying updated with emerging topics and trends in midazolam research is crucial for guiding future investigations and informing clinical practice.